Patients need to know that ileostomy following anterior resection may not be reversed - Ng, Jing-Yu; Koh, Frederick H.; Yeo, Danson; Ng, Sheldon Jin-Keat; Tan, Kok-Yang; Tan, Ker-Kan (International Surgery Journal, 2018)
Background: A diverting ileostomy is often created following a low colorectal anastomosis to reduce the clinical consequences of an anastomotic leak. Whilst many patients are advised that these ileostomies are temporary, not all stomas will eventually be closed. This study aimed to look at the reversal rates of diverting ileostomy following anterior resections, and the reasons for delayed or non-reversal. Methods: A retrospective review of all patients who underwent an anterior resection with a diverting ileostomy from March 2011 to March 2013 was performed. Results: A total of 115 patients had a diverting ileostomy following anterior resection within the study period. Seventy-six (66.1%) patients had a reversal before March 2016. The median time to reversal was 8 months (range, 1-26 months) with only 13% reversed within 12 weeks. Two patients (2.6%) had anastomotic leaks post ileostomy reversal requiring surgery and 1 patient (1.3%) had significant hematochezia requiring hospitalization. In the 39 (33.9%) patients who did not have their ileostomies reversed, deterioration in the fitness of the patient for surgery was the most commonly cited reason (n=12, 30.8%). This was followed by disease progression (n=9, 23.1%) and patient’s choice (n=8, 20.5%). Conclusions: One in 3 diverting ileostomies performed following anterior resection is not reversed. The interval time to its closure is longer than typically expected. Patients should be made aware of the significant possibility of non-reversal.